2022
DOI: 10.3390/nu14194155
|View full text |Cite
|
Sign up to set email alerts
|

Ergogenic Effects of Caffeine on Ballistic (Throwing) Performance: A Meta-Analytical Review

Abstract: Ballistic exercise is characterized by high velocity, force, and muscle activation. Typical examples of ballistic exercise are jumping and throwing activities. While several studies explored caffeine’s effects on throwing performance, the between study findings varied. Therefore, we performed a meta-analysis exploring caffeine’s effects on throwing performance (e.g., shot put, medicine ball throw, bench press throw). Seven databases were searched for eligible research. Ten studies (n = 151) were included. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
2
1
Order By: Relevance
“…Consistently with these results, a study showed that consuming 150 mg of caffeine as chewing gum had no significant effect on the power and isometric handgrip strength of basketball players [ 34 ]. However, inconsistency with the present results, it had been shown in a meta-analysis that caffeine consumption increased the throwing performance of athletes [ 29 ]. The proposed mechanisms that may explain the energizing effects of caffeine are improving neuromuscular function, increasing endorphin secretion, improving alertness and reducing activity perception during exercise [ 46 ].…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Consistently with these results, a study showed that consuming 150 mg of caffeine as chewing gum had no significant effect on the power and isometric handgrip strength of basketball players [ 34 ]. However, inconsistency with the present results, it had been shown in a meta-analysis that caffeine consumption increased the throwing performance of athletes [ 29 ]. The proposed mechanisms that may explain the energizing effects of caffeine are improving neuromuscular function, increasing endorphin secretion, improving alertness and reducing activity perception during exercise [ 46 ].…”
Section: Discussioncontrasting
confidence: 97%
“…Explosive power of upper body muscles: A 3 kg medicine ball was used, and the participants threw the ball three times in front of their chest, and their best record was recorded in centimeters [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, the changes (relative percentage) compared with PLA showed that right handgrip strength (C3: 4.9% and C6:3.54%), upper-body explosive power (C3: 3.28% and C6: 3.38%), and hand movement speed (C3: 6.11% and C6: 6.02%) improved after caffeine supplementation. Consistent with these findings, A meta-analysis also showed that caffeine improved throwing performance with a small effect size, especially when the supplemental dose was ≤3 mg/kg BW [ 60 ]. Another study has also shown that caffeine has a small effect size on improving grip strength regardless of dosage [ 61 ].…”
Section: Discussionmentioning
confidence: 71%